2019
DOI: 10.3126/njc.v3i1.25914
|View full text |Cite
|
Sign up to set email alerts
|

Enterostomal Therapy Service: Ten-year Experience at B.P. Koirala Memorial Cancer Hospital

Abstract: Introduction: Enterostomal therapy (ET) is the newly evolving subspecialty area of nursing. None of the university started the ET courses in Nepal. Very few ET nurses catering the needs of osteomates in different hospital. Increasing burden of colorectal and urinary bladder cancer increases the ostomy population. There are no definite data regarding the ostomy population in national context. So, this is the neglected area of care in most cancer hospital of Nepal. The objective of this study is to find out the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Nursing care for breast cancer patients focused on lymphedema prevention and its management. Stoma creating surgery emphasized the care of stoma, prevention of peristomal skin complications, foul order control, leakage control, appropriate use of ostomy appliances, and colostomy irrigation 5 . The role of enterostomal therapist (ET) was recognized by Norma Gill and Dr. Turnbull in 1954, then in 1961 opened the school for enterostomal therapist in Cleveland clinic to increase the number of enterostomal therapist.…”
Section: Bpkmchmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing care for breast cancer patients focused on lymphedema prevention and its management. Stoma creating surgery emphasized the care of stoma, prevention of peristomal skin complications, foul order control, leakage control, appropriate use of ostomy appliances, and colostomy irrigation 5 . The role of enterostomal therapist (ET) was recognized by Norma Gill and Dr. Turnbull in 1954, then in 1961 opened the school for enterostomal therapist in Cleveland clinic to increase the number of enterostomal therapist.…”
Section: Bpkmchmentioning
confidence: 99%
“…In contrary, these specialist job was very effort consuming due to unavailability of different appliances and modern dressing materials in our part of the world which has demotivated those nurses to carry their jobs. 5 Another important role of the nurse is as a counselor, especially for the patient who underwent stomy surgery, vulvectomy, penectomy, limb amputation, mastectomy, and other physically disfiguring surgical procedure. It was found that dealing with a patient who lost the selfrespect and body image is very tough.…”
Section: Bpkmchmentioning
confidence: 99%